Minority Shareholders' Control Rights and the Quality of Corporate Decisions in Weak Investor Protection Countries: A Natural Experiment from China - Chen, Zhihong; Ke, Bin; Yang, Zhifeng (The Accounting Review, 2013)
ABSTRACT Using a 2004 Chinese securities regulation that requires equity offering proposals to obtain the separate approval of voting minority shareholders, we examine whether giving minority shareholders increased control over corporate decisions helps to reduce value-decreasing corporate decisions for firms domiciled in weak investor protection countries. We find that the regulation deters management from submitting value-decreasing equity offering proposals in firms with higher mutual fund ownership. There is also weak evidence that minority shareholders are more likely to veto value-decreasing equity offering proposals in firms with higher mutual fund ownership in the post-regulation period. Overall, our evidence suggests that in weak investor protection countries, the effect of granting minority shareholders increased control over corporate decisions on the quality of corporate decisions depends on the composition of minority shareholders. JEL Classifications: G32; G34; G38